Ganti Rugi Atas Kebakaran Gunung Bromo Disebabkan Pengguna Flare Pada Saat Foto Prewedding Perspektif Wahbah Az-Zuhaili - Ima Arti Cahyani Sipayung; Zulham Zulham (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The Mount Bromo fire caused by the use of flares during prewedding photos raises questions about compensation. The purpose of this research is to find out how compensation for the Mount Bromo Fire Caused by Flare Users During Prewedding Photos in the Perspective of Wahbah Az-Zuhaili. The method used in this research is the normative method, to analyze the obligation of compensation based on positive law in Indonesia. The results of this study are according to the Law Regulations based on the Criminal Code, flare users can be convicted and charged compensation, especially since this fire case was caused by negligence that harmed many parties including the Indonesian state, and has harmed the state budget, nature, and surrounding residents. Meanwhile, according to Wahbah Az-Zuhaili, compensation must be based on the principles of ta'zir and ta'widh. A fair compensation solution can be sought through consensus deliberation involving all relevant parties.